We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
492
1
avatar

Find (a,b) such that \(L_n = a\phi^n + b\widehat{\phi}^n\)

 May 23, 2018
 #1
avatar+21991 
0

Find (a,b) such that 

\(L_n = a\phi^n + b\widehat{\phi}^n\)

L_n = a\phi^n + b\widehat{\phi}^n

 

\(\begin{array}{|rcll|} \hline L_n &=& \phi^n + \widehat{\phi}^n \\\\ (a,b) &=& (1,1) \\ \hline \end{array}\)

 

laugh

 May 24, 2018

22 Online Users

avatar